The Effectiveness of Aesthetic Teaching on the Attitude of Elementary School Students - Ahmad Ahmadi; Roohallah Fathabadi; Morteza Bakhtiarvand (RIRAI Publisher, 2020)
The aim of this study was to investigate the effect of aesthetics based teaching on students' attitudes toward school. This is an all-experimental study of pre-test-post-test design with a control group. The statistical population of sixth grade students in schools Fardis in the academic year of 1997-98 was. The sampling method was simple random and the selected students were divided into experimental and control groups. The sample size was determined using Morgan table and the number of sample people in each group was 16. Experimental science course was taught in the experimental group by aesthetic teaching method and in the control group by traditional teaching method. To assess the attitude towards school, McCoach (2003) school attitude questionnaire (SAAS-R) was used with a reliability of 0.96. The obtained data were analyzed by multivariate analysis of covariance. The results showed that the level of attitude towards school in students who took the sixth grade experimental sciences course with aesthetic methods was different from the students who learned this course with the usual teaching methods in schools. Therefore, the aesthetic method can play a role as an active and effective method in students' academic achievement in science.